Magnitude and Determinant Factors of Herbal Medicine Utilization Among Mothers Attending Their Antenatal Care at Public Health Institutions in Debre Berhan Town, Ethiopia - Wake, Getu Engida; Fitie, Girma Wogie (Frontiers in Public Health, 2022)
Abstract Background: World health organization defined herbal medicines as a practice of herbs, herbal materials, herbal preparations, and finished herbal products. Globally women are the primary utilizer of herbal medicine and even they consume it during their pregnancy period. The World health organization reported that the majority of the global population used traditional medicine. This study aimed to assess the magnitude and determinant factors of herbal medicine utilization among pregnant mothers attending their antenatal care at public health institutions in Debre Berhan town, Ethiopia. Methodology: Institution-based cross-sectional study was conducted among pregnant mothers who attended their antenatal care at public health institutions in Debre Berhan town, Ethiopia from12 February 2021 to 12 April 2021. A systematic random sampling method was used to get selected pregnant mothers. Epi data version 3.1and and SPSS version 25 were used for data entry and analysis respectively. P-value ≤ 0.05 was used as a cut point of statistical significance in multivariable binary logistic regression. Results: A total of 422 pregnant mothers were included with a 100% response rate and 277(65.6%) of them used herbal medicine during their current pregnancy. Educational level up to primary school [AOR 2.21, 95% CI: 1.17-4.18], monthly family income of less than 2800 ETB [AOR 1.72, 95% CI: 1.01-2.92], and lack of awareness on the complication of herbal medicine utilization [AOR 10.3, 95% CI: 6.27-16.92] were determinant factors of herbal medicine utilization. Conclusion: The utilization of herbal medicine among pregnant mothers in this study is high and almost all of them didn’t disclose utilization of herbal medicine to their health care providers. The ministry of health should integrate traditional medicine with conventional medicines. Midwives and obstetricians should openly discuss regarding benefits and complications of herbal medicine utilization for those pregnant mothers during their antenatal care counseling session as routine care.